EU's metaphorical representation in the Moldovan economic press - Magdalena Danilet; Olesia Mihai; Anca Maria Clipa (CES Working Papers, 2017)
The study aims to identify the metaphors associated with the EU in the economic press published in Romanian and Russian languages in the Republic of Moldova after signing the Association Agreement (AAs). It set out to answer the following research questions: How Moldovan economic newspapers frame the EaP issues through metaphors? Are these metaphors meant to increase the EU appeal to readers of economic newspapers? For this purpose, we conducted a quantitative and qualitative content analysis of a corpus of Moldavian economic newspapers in order to identify the EU-based metaphors.
Keywords: M31; Y8; 330; content analysis; metaphor; economic press; European Union; Republic of Moldova